The Effect and Potential of Digital Health in The Cycle of Care in Tuberculosis Patients from Low and Middle-income Countries - le Roux, Jacobus Johannes (Department of Human Biology, 2022)
Background LMICs account for approximately 87% of all new TB cases. Effective TB management is vital if the global end TB goals are to be achieved by 2035. The role of digital health (DH) interventions in achieving these goals are pertinent. TB treatment adherence is considered to be critical not only in successful eradication of the disease, but also in the containment of drug-resistant strains of the disease. This review set out to assess the effect of DH interventions on TB patient treatment adherence in LMICs. Methods A systematic review was conducted by searching various databases (Pubmed, Scopus, EBSCOhost Web of Science) as well as grey literature sources for literature incorporating randomized controlled trials (RCTs), cohort, or cross-sectional studies which assessed DH interventions aimed at improving TB patient treatment adherence within LMICs. Studies were included if they were reported primary outcomes related to patient treatment adherence and were published in English before 30 November 2020. The risk of bias was independently assessed using the Cochrane Risk of Bias Assessment Tool. Results Out of the 1030 articles identified through the databases, 41 articles were full text screened and eleven included in the synthesis of this review. Seven studies utilized text-based reminders, two employed electronic medication monitors, and two employed call reminders, and one involved video observed therapy (VOT). Grouped analysis of all included studies yielded a marginal improvement in positive patient treatment outcomes (RR 1.05, 95% CI 1.02 - 1.09). Conclusion DH interventions show promise in improving patient adherence and positive treatment outcomes. Current available literature remains scarce and of questionable quality. Studies incorporating a patient-centred approach which is executed according to standardized implementation procedures and outcome assessment is required.